Africa Yearbook Volume 20 : Politics, Economy and Society South of the Sahara in 2023 - Alidu, Seidu M.,; Kamski, Benedikt,; Mehler, Andreas,; Sebudubudu, David, (Africa Yearbook ;, 2025)
The Africa Yearbook covers major domestic political developments, the foreign policy and socio-economic trends in sub-Sahara Africa - all related to developments in one calendar year. The Yearbook contains articles on all sub-Saharan states, each of the four sub-regions (West, Central, Eastern, Southern Africa) focusing on major cross-border developments and sub-regional organizations as well as one article on continental developments and one on African-European relations. While the articles have thorough academic quality, the Yearbook is mainly oriented to the requirements of a large range of target groups: students, politicians, diplomats, administrators, journalists, teachers, practitioners in the field of development aid as well as business people.